2006
DOI: 10.1007/s10840-006-9034-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of cardiac markers for myocardial damage after radiofrequency catheter ablation

Abstract: h-FABP is an insensitive and less specific marker of myocardial damage in RFCA much along the lines of CK-MB and when compared with the proven accuracy of cTnT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
0
23
0
3
Order By: Relevance
“…Similar elevations in troponin T have also been demonstrated, but correlation to specific parameters of the electrophysiological procedure is less consistent (321,322). In all of these studies, patients suffered no complications requiring further intervention.…”
Section: Appendix 1 Relevant Author Relationships With Industry and mentioning
confidence: 60%
“…Similar elevations in troponin T have also been demonstrated, but correlation to specific parameters of the electrophysiological procedure is less consistent (321,322). In all of these studies, patients suffered no complications requiring further intervention.…”
Section: Appendix 1 Relevant Author Relationships With Industry and mentioning
confidence: 60%
“…In our study, the higher cTnI and CK-MB levels in cryoballoon group may be explained by longer energy delivery duration compared to the other groups. Previous AF ablation studies have found a correlation between levels of cTnT and RF delivery duration and cumulative RF energy [24,27,28], but no data exist regarding other energy sources. Apart from the energy delivery duration, other factors may contribute to higher degree of myocardial injury in cryoablation, as suggested by increased levels of biomarkers post ablation.…”
Section: Previous Studiesmentioning
confidence: 99%
“…However, RFCA causes some myocardial damage at the site where the catheter tip contacts tissue. This damage may include lipid membrane disruption and metabolic and structural protein inactivation and denaturation, as well as nuclear damage (99 ). In a study of 60 patients undergoing RFCA who had no underlying structural heart disease, all patients were found to have increased postprocedure cardiac cTn, with all measurements exceeding the diagnostic threshold for MI (100 ).…”
Section: Other Medications Wallace Et Al (143 )mentioning
confidence: 99%